Dark Energy from α-attractors: Phenomenology and Observational Constraints - Garcia-Garcia, Carlos; Linder, Eric V.; Ruiz-Lapuente, Pilar; Zumalacaregui, Miguel (NURIS; Energetic Cosmos Laboratory, 2018)
The possibility of linking inflation and late cosmic accelerated expansion using the α-attractor models has received increasing attention due to their physical motivation. In the early universe, α-attractors provide an inflationary mechanism compatible with Planck satellite CMB observations and predictive for future gravitational wave CMB modes. Additionally α-attractors can be written as quintessence models with a potential that connects a power law regime with a plateau or uplifted exponential, allowing a late cosmic accelerated expansion that can mimic behavior near a cosmological constant. In this paper we study a generalized dark energy α-attractor model. We thoroughly investigate its phenomenology, including the role of all model parameters and the possibility of large-scale tachyonic instability clustering. We verify the relation that 1+w∼1/α (while the gravitational wave power r∼α) so these models predict that a signature should appear in either the primordial B-modes or in late time deviation from a cosmological constant. We constrain the model parameters with current datasets, including the cosmic microwave background (Planck 2015 compressed likelihood), baryon acoustic oscillations (BOSS DR12) and supernovae (Pantheon compressed). Our results show that expansion histories close to a cosmological constant exist in large regions of the parameter space, not requiring a fine-tuning of the parameters or initial conditions.
Energetic Cosmos Laboratory. ECL Publication
Keywords: The 2nd international conference of the Energetic Cosmos Laboratory (ECL); Energetic Cosmos Laboratory (ECL); ECL19